Multicomponent Click Synthesis of 1,2,3-Triazoles from Epoxides in Water Catalyzed by Copper Nanoparticles on Activated Carbon - Alonso, Francisco (2011)
Copper nanoparticles on activated carbon have been found to effectively catalyze the multicomponent synthesis of β-hydroxy-1,2,3-triazoles from a variety of epoxides and alkynes in water. The catalyst is easy to prepare, reusable at a low copper loading (0.5 mol %), and exhibits higher catalytic activity than some commercially available copper sources. The regio- and stereochemistry of the reaction has been revised and unequivocally established on the basis of X-ray crystallographic analyses. An NMR experiment has been implemented for the rapid and unmistakable determination of the regiochemistry of the process. Some mechanistic aspects of the reaction have been also undertaken which unveil the participation of copper(I) acetylides.